2014
DOI: 10.1186/scrt397
|View full text |Cite
|
Sign up to set email alerts
|

Human cadaver multipotent stromal/stem cells isolated from arteries stored in liquid nitrogen for 5 years

Abstract: IntroductionRegenerative medicine challenges researchers to find noncontroversial, safe and abundant stem cell sources. In this context, harvesting from asystolic donors could represent an innovative and unlimited reservoir of different stem cells. In this study, cadaveric vascular tissues were established as an alternative source of human cadaver mesenchymal stromal/stem cells (hC-MSCs). We reported the successful cell isolation from postmortem arterial segments stored in a tissue-banking facility for at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 37 publications
5
35
0
Order By: Relevance
“…26 A previous study showed that human cadaveric MSCs stored in liquid nitrogen for 5 y retained the ability to express VWF and CD31, supporting the commitment toward the endothelial cell lineage. 2 The above data suggests that human stem cells maintain their differentiation potential post mortem. In our study, we found that TNI expression even increased in the 24 h group compared to the 0 h group.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…26 A previous study showed that human cadaveric MSCs stored in liquid nitrogen for 5 y retained the ability to express VWF and CD31, supporting the commitment toward the endothelial cell lineage. 2 The above data suggests that human stem cells maintain their differentiation potential post mortem. In our study, we found that TNI expression even increased in the 24 h group compared to the 0 h group.…”
Section: Discussionmentioning
confidence: 92%
“…Mesenchymal stem cells (MSCs), skeletal muscle stem cells, and hepatic stem cells could be cultured from cadaveric organs and tissues while maintaining viability. [2][3][4] Successful isolation, propagation, functional characterization, and cryopreservation of human cadaveric MSCs derived from variously sized arterial segments 4 d post mortem have been maintained for more than 5 y. 2 Latilet et al 3 confirmed that viable and functional skeletal myogenic cells can be obtained from humans up to 17 days, and from mice up to 14 d post mortem.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…18,19 This population shares properties of human bone marrow mesenchymal cells with stemness features, as well as with the ability to survive and be enriched under anoxia and cryoinjury post mortem stresses. 20 This same cell population also had the ability to modulate immune response through the suppression of immune cell activation and proliferation. 20, 21 This study aimed to detect the presence of mesenchymal stromal (stem) cells (MSCs) in AAAs and explore their potential involvement in ECM degradation and inflammation.…”
Section: Editorial P 1439mentioning
confidence: 99%
“…These properties, together with a transcriptional profile typical of embryonic stem cells; that is, expression of the transcriptional factors, Nanog, Oct-4, Sox-2, are well-expressed by a population of multipotent stromal cells recently isolated from the vascular wall of multiorgan donors. 19, 20 Pathological vascular tissues were collected from 12 patients undergoing vascular repair for AAA disease; we succeeded in obtaining a cell population that in vitro had growth characteristics; that is, fibroblast morphology and growing kinetic, sim-…”
Section: -17mentioning
confidence: 99%